Le roman de l’homme : Bartolomé Bennassar et la narration des biographies d’Ancien Régime - Alain Hugon (Les Cahiers de Framespa)
Bartolomé Bennassar wrote four biographies of men from the 16th and 17th centuries and in his other books, he never stopped placing “the lives of men” at the heart of his analyses. The centrality of the individual within B. Bennassar's historical discourse is reflected in the multiplication of biographical uses in his developments and arguments. In monographs devoted to a single historical figure, he used original narrative processes to convey his own perception of the "great man".